Collaborative Governance in Improving the Quality of Digital Population Identity Services in Central Mamuju Regency - Hasanuddin; Daswati; M. Nur Alamsyah; Ani Susanti (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research aims examine the application of collaborative governance in improving the quality of digital identity services in Central Mamuju Regency. This research focuses on collaboration which is designed using a qualitative approach. The informants of this research consisted of internal and external parties of the Population and Civil Registration Office of Mamuju Tengah Regency which were determined purposively. External parties are partners of the agency in implementing digital identity in Central Mamuju Regency. Data collection techniques include observation, in-depth interviews, and documentation, while the data analysis of this research uses an interactive approach which includes data collection, data condensation, data presentation, and conclusion drawing. The results showed that inter-stakeholder collaboration is still at a very early stage and has not been effective in driving significant implementation achievements. The realization of the Digital Population Identity program, which only reached 2% of the target, indicates a weak integration between unsupportive initial conditions, poorly structured institutional design, un-transformative leadership, and the lack of participatory and inclusive collaborative processes. This finding reinforces the assumption in collaborative governance theory that the success of a public program, especially one that is cross-sectoral and based on digital technology, is largely determined by structural readiness, clarity of institutional roles, and the presence of leadership that is able to mobilize synergies and create a shared deliberative space